Magnetic resonance imaging of aqueductal flow in patients with normal hydrocephalus pressure. - Matias, S; Ferreira, T; Vilela, P; Secca, M; Goulão, A (Acta Médica Portuguesa, 2001)
The treatment of patients with the so-called Normal Pressure Hydrocephalus (NPH) consists of ventricular shunting, but only in some cases is there clinical improvement. The selection of patients for ventricular shunting is usually based on the response to the evacuating lumbar punctures of the cerebrospinal fluid (CSF), but new MRI techniques of flow measurement have been used successfully. In this study, a group of 58 patients, 28 of which with NPH, is presented. Flow quantification of the aqueductal CSF using the MR Phase Contrast technique was performed in all of them. The authors conclude that the method is sensitive and can be a valid criterium in the selection of patients for ventricular shunting.